A new seco-pimarane diterpene and four new β-resorcylic acid lactones from a fungicolous Hypomyces subiculosus. Issue 82 (9th November 2017) - Liu, Li; Liu, Ruixing; Basnet, Buddha Bahadur; Bao, Li; Han, Junjie; Ren, Jinwei; Zeng, Zhaoqing; Zhuang, Wenying; Liu, Hongwei
Abstract : One new seco-primarane diterpene and four new β-resorcylic acid lactones were isolated and identified from the fungicolous Hypomyces subiculosus . Abstract : One new pimarane diterpene (1 ) and four new β-resorcylic acid lactones (2–5 ), together with eight known compounds (6–13 ) were isolated from the solid culture of the fungicolous Hypomyces subiculosus . The structures of the new compounds were elucidated using extensive spectroscopic methods, including 1D and 2D NMR, HRESIMS, CD experiments, and chemical means. Compound1 is a ring cleavage pimarane diterpene possessing a bicyclic ring system. All compounds were evaluated for cytotoxic activities. Only compound7 showed moderate cytotoxicity against the A549 cell line with an IC50 of 44.5 μM.